Trough of low pressure over the Gangetic Valley during the southwest monsoon season and its implications -A suggested new approach (MAUSAM, 1967)
Current ideas about the trough of low pressure over the Gangetic Valley, facts of weather and chimatology during the southwest monsoon season and the role of the topographical features of the Indo-Pakistan subcontment in the formation of the trough, have been stated briefly. A new approach about the establishment of the trough is suggested and implications of the same are discussed.